2019
DOI: 10.1016/j.gca.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine partitioning between granitic melt and H2O-CO2-NaCl fluids in the Earth’s upper crust and implications for magmatic-hydrothermal ore genesis

Abstract: Chlorine partitioning between granitic melt and H 2 O-CO 2-NaCl fluids in the Earth's upper crust and implications for magmatic-hydrothermal ore genesis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…The Quizapu dataset for instance, has similar values to those ofAlletti et al (2009) andBotcharnikov et al (2015), yet higher than others(Zajacz et al, 2012). Kelud's experimental glass composition also overlapped with other studies(Hsu et al, 2019;Webster et al, 2017;Webster & Holloway, 1990) and provides similar partitioning values. The literature data for CO 2 mixed volatile experiments on figure8are plotted as open…”
supporting
confidence: 77%
See 2 more Smart Citations
“…The Quizapu dataset for instance, has similar values to those ofAlletti et al (2009) andBotcharnikov et al (2015), yet higher than others(Zajacz et al, 2012). Kelud's experimental glass composition also overlapped with other studies(Hsu et al, 2019;Webster et al, 2017;Webster & Holloway, 1990) and provides similar partitioning values. The literature data for CO 2 mixed volatile experiments on figure8are plotted as open…”
supporting
confidence: 77%
“…Webster. Chlorine fluid/melt partitioning (D Cl fluid/melt ) behaviour has been quantified for a range of silicate melt compositions (Webster and Holloway 1990;Webster 1997;Webster et al 2014), pressures (Alletti et al 2009;Botcharnikov et al 2015;Webster et al 2017), temperatures (Stelling et al 2008), ƒO 2 (Beermann et al 2015), and volatile contents (Lowenstern 1994;Botcharnikov et al 2006;Alletti et al 2009;Webster et al 2014;Hsu et al 2019). Fluorine, a relatively difficult element to measure in silicate glass (due to elemental interferences on the electron microprobe), has received less study, with most experiments focusing on end-member silicic or alkaline magmas (figure 1) (Webster and Holloway 1990;Borodulin et al 2009;Iveson et al 2017) and few data available for mafic and intermediate magmas (Chevychelov et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the H 2 O concentrations in even primitive arc magmas may reach ≥6 wt% H 2 O 31,49,51 -enough to saturate H 2 O by the mid-crust when accounting for the elevation in H 2 O concentrations accompanying the amount of crystallization needed to derive mafic basaltic andesite compositions. There may be a delicate balance for efficient Cl degassing, as recent experiments using rhyolitic melts have shown that CO 2 can hinder Cl partitioning into magmatic fluids at upper crustal pressures 52 , although the higher density of fluid degassed at greater depth may partially mitigate this. We currently lack the experimental data to properly model these specific scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a regional contact-type of metamorphism can be one type of thermal event leading to the required devolatilization of the country rocks. Some experimental results have been suggested as providing indirect evidence of a magmatic-hydrothermal origin for some orogenic gold through the recognition that CO 2 -rich fluids exsolve from hydrous magmas at mid-crustal depths and earlier stages of magmatic evolution (Hsu et al 2019). But, as we argue above, other experimental work suggests large fluid volumes are most commonly not released from melts until they reach the upper 6 km; magma degassing at greater depths tends to focus volatiles upward within channels in the magmatic system; and much of the Au and H 2 S remain in the system until melts stall at about 3-6 km.…”
Section: Discussionmentioning
confidence: 99%